2021
DOI: 10.1371/journal.pone.0254189
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome analysis of bread wheat leaves in response to salt stress

Abstract: Salinity is one of the main abiotic stresses limiting crop productivity. In the current study, the transcriptome of wheat leaves in an Iranian salt-tolerant cultivar (Arg) was investigated in response to salinity stress to identify salinity stress-responsive genes and mechanisms. More than 114 million reads were generated from leaf tissues by the Illumina HiSeq 2500 platform. An amount of 81.9% to 85.7% of reads could be mapped to the wheat reference genome for different samples. The data analysis led to the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 102 publications
1
20
0
Order By: Relevance
“…Wheat constitutes pivotal position for ensuring food and nutritional security; however, rapidly rising soil and water salinity pose a serious threat to its production globally. Salinity stress negatively affects the growth and development of wheat resulting in restrained grain yield and quality [ 30 , 31 ]. Hence, improving wheat salt tolerance and exploiting arable areas of saline soils are becoming the most important scientific research and agricultural practices.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wheat constitutes pivotal position for ensuring food and nutritional security; however, rapidly rising soil and water salinity pose a serious threat to its production globally. Salinity stress negatively affects the growth and development of wheat resulting in restrained grain yield and quality [ 30 , 31 ]. Hence, improving wheat salt tolerance and exploiting arable areas of saline soils are becoming the most important scientific research and agricultural practices.…”
Section: Discussionmentioning
confidence: 99%
“…Among various food crops, wheat ( Triticum aestivum L.) is a staple food in 30% of the world. However, it faces severe losses in its productivity due to salt stress [ 30 , 31 ]. Development of salt-tolerant wheat cultivars adapted to saline conditions is the most effective and economic strategy to combat this detrimental phenomenon.…”
Section: Introductionmentioning
confidence: 99%
“…It is a complex abiotic stress that causes nutritional imbalances, particular ionic effects, and osmotic stress. For defense, plants minimize the entry of salt ions into the cytoplasm and/or enhance the synthesis of osmolytes, antioxidants, and phytohormones [ 2 , 3 , 4 ]. Salt stress also induces the over-production of reactive oxygen species (ROS) causing oxidative stress that impairs cellular homeostasis.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, RNA-seq analysis based DEGs and candidate gene identification has been used to study salt tolerance in numerous plants, including Arabidopsis ( Sako et al, 2021 ), rice ( Chandran et al, 2019 ), bread wheat ( Amirbakhtiar et al, 2021 ), Chinese cabbage ( Li et al, 2021 ), drought/salt-tolerant Caragana korshinskii ( Li et al, 2016 ), a model halophytic Chenopodium quinoa ( Ruiz et al, 2019 ), Cenostigma pyramidale ( Frosi et al, 2021 ), and Ricinus communis ( Lei et al, 2021 ). These studies have identified abundant DEGs, candidate upregulated genes, and the functional enrichment of GO terms and pathways related to salt stress responses in plants.…”
Section: Discussionmentioning
confidence: 99%